2020
DOI: 10.3889/oamjms.2020.4760
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and Cell Cycle Pathway-Focused Genes Expression Analysis in Patients with Different Forms of Thyroid Pathology

Abstract: BACKGROUND: Thyroid hormones are key regulators of essential cellular processes including proliferation, differentiation, and finally apoptosis. AIM: The aim of study was to detect changes in the expression of apoptosis and cell cycle pathway-focused genes in patients with different forms of thyroid pathology. PATIENTS AND METHODS: 36 patients with thyroid pathology were enrolled in the study. We used the pathway-specific real-time PCR array (Neurotrophins and Receptors RT2 Profiler PCR Array, QIAG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…A significant factor involved in the induction of autoimmune response is a defect in or deficiency of the immune regulation, particularly disequilibrium between the effector T cells (Teff) and regulatory T cells (Treg) which normally prevent the development of autoimmunity (2,3). Multiple susceptibility genes may be involved in the disease development, some of which are also implicated in other autoimmune diseases (4,5), while others are specific to thyroid autoimmunity (6,7). However, data about the expression of сytokines and cytokine receptor pathway-focused genes in patients with different forms of thyroid pathology from Europe are limited, and no such data from Ukraine has been internationally published.…”
Section: Introductionmentioning
confidence: 99%
“…A significant factor involved in the induction of autoimmune response is a defect in or deficiency of the immune regulation, particularly disequilibrium between the effector T cells (Teff) and regulatory T cells (Treg) which normally prevent the development of autoimmunity (2,3). Multiple susceptibility genes may be involved in the disease development, some of which are also implicated in other autoimmune diseases (4,5), while others are specific to thyroid autoimmunity (6,7). However, data about the expression of сytokines and cytokine receptor pathway-focused genes in patients with different forms of thyroid pathology from Europe are limited, and no such data from Ukraine has been internationally published.…”
Section: Introductionmentioning
confidence: 99%
“…“Peripheral marker hypothesis” revealed that gene expression changes in some regions of the brain are reflected into the peripheral blood lymphocytes [ 10 ]. Transcriptome analysis is indicative of gene functional activity [ 11 , 12 ]. In our study, we used polymerase chain reaction (PCR) arrays to compare gene expression data, which enables understanding of the influence of thyroid hormones and serum autoantibodies, such as an anti-thyroglobulin antibody (anti-Tg) and anti-thyroid peroxidase antibody (anti-TPO) on the mRNA neuropeptides and receptors pathway-focused gene expression in patients with primary hypothyroidism resulted from AIT and postoperative hypothyroidism and patients with AIT with rising serum autoantibodies, such as anti-Tg and anti-TPO.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we demonstrated that autoimmune thyroiditis (AIT) and hypothyroidism can affect the transcription of mRNA for the genes involved in nerve impulse transmission and cell cycle in a genespecific manner [5], [6], [7]. These changes in gene expression can also play a role in the development of neurological complications related to thyroid pathology, but the model of neurotrophin expression and its regulation under pathological conditions is not yet complete.…”
Section: Introductionmentioning
confidence: 99%